INTESTINAL BACTERIA (International journal of artificial intelligence, 2026)
This article describes in detail the general biological characteristics of microorganisms belonging to the Enterobacteriaceae family, the similarities and differences in their morphological, cultural, and tinctorial characteristics. Bacteria belonging to this family are widespread in nature, living mainly in the intestinal tract of humans and animals and are excreted into the external environment through feces. The article analyzes the epidemiological significance of pathogenic representatives such as Escherichia coli, Salmonella, Shigella, and Klebsiella, their routes of entry into the human body, mechanisms of pathogenesis, and clinical manifestations. The role of Escherichia coli as an opportunistic pathogen, its role in the normal intestinal microflora, vitamin synthesis, and its antagonistic effect on other microorganisms have also been scientifically elucidated. In addition, the causes of dysbacteriosis, the consequences of intestinal microflora imbalance, and the mechanisms of the occurrence of diseases such as salmonellosis and shigellosis are highlighted. Special attention was paid to preventive measures, emphasizing the importance of adhering to sanitary and hygienic rules, controlling sources of infection, and using vaccines and antibacterial drugs.